Unity In Diversity: Moving Indonesian Theater, Film, and Television Forward - Eka Dimitri Sitorus (Jurusan Pendidikan Seni Pertunjukan ISI Yogyakarta, 2021)
AbstractThe purpose of this article is to show how Indonesia has experienced a tremendous change in its approach to acting in the last 20 years, but it has not been for the better. The modern era of film and television has led to a misleading perception among the Indonesian people regarding the art of “acting,” thereby resulting in an unfavorable attitude toward the craft. This misleading perception stems from the effect of traditional Indonesian theater to its modern counterpart without any adjustments to cater to the millennial generation of Indonesians. The paper explores the roots of this misleading perception. It starts with the problem of applying Indonesian cultural policy, catering to such diverse artistic expressions in Indonesia, educating the artists, all the way to providing the specific educational infrastructure for the arts. The article provides examples of past theater and film productions to point out the problems of modern versus traditional acting styles, the challenges of translations of classic and contemporary western plays into the Indonesian language, the difficulties to apply such rigid interpretations by prominent Indonesian writer to contemporary Indonesian acting styles. The article shows that only by improving and implementing sound Indonesian cultural policy, developing and managing specific educational infrastructure for the arts, and creating a new acting method or re-considering the pre-existing ones, the Indonesian theatre, film, and television will be able to move forward.